A kidney transplant recipient with recurrent trichilemmal carcinoma and multiple other primary malignancies - Grossberg, Saul J; Diana, Nina E (African Journal of Nephrology, 2020)
Kidney transplant recipients are at increased risk of developing malignancy, with prolonged immunosuppressive therapy being a strong risk factor. Non-melanoma skin cancers are most commonly reported and multiple primary malignancies are also described. This is the first report of a recurrent trichilemmal carcinoma, a rare cutaneous tumour, in a kidney transplant recipient. This case, and the associated literature, indicate that regular screening, thorough examination, and tailored immunosuppressive regimens are critical in managing these patients.